Mechanics and muscular activity characteristics of the pinch grip across varying hold widths and climber skill levels - Huang, Y.; Li, S.; Peng, Y.; Yu, J.; Chen, R.; Ding, X.; Hao, W. (Journal of Sports Sciences, 2026)
This study aims to explore the mechanics and muscular activity characteristics of the pinch grip across varying hold widths and climber skill levels. Upper-ranked (n = 11) and lower-ranked (n = 11) advanced climbers completed maximum gripping biomechanical test of a jug hold and two pinch holds with different widths. The resultant traction force, traction force components, the utilization rates of traction forces, hand normal pressing force and root mean square (RMS) amplitude of upper limb muscles were collected. Compared to the jug, traction force decreased by 6%-19% when using the broad pinch and 31%-46% with the narrow (all P < 0.001). The RMS of the pectoralis major, biceps brachii, and latissimus dorsi also showed the pattern the jug > the broad pinch > the narrow pinch (all P < 0.01). Traction force utilization rates at the broad pinch were 21%-62% higher than at the narrow pinch (all P < 0.001). The upper-ranked group showed significantly greater traction forces and higher hand normal pressing force compared to the lower-ranked (all P < 0.01). Holds` width is a significant factor in the biomechanical characteristics of pinch. Upper-ranked advanced climbers demonstrate higher hand normal pressing forces and traction forces compared to the lower-ranked.